KNOWLEDGE AND CHARACTERISTICS DO NOT AFFECT THE STRESS OF MOTHERS CARING FOR AUTISTIC CHILDREN IN INDONESIA: A CROSS-SECTIONAL STUDY - Nazhifah, Hana Najla; Sianturi, Renta (Journal of Community Mental Health and Public Policy, 2025)
Background: Autistic Spectrum Disorder is an incurable developmental disease. Parents who have autistic children must have the ability to care for them because they have differences especially in socializing, so parents experience stress in caring for them. Purpose: To analyze the relationship between the characteristics and level of knowledge of mothers with the level of stress in caring for children with autism in bekasi city. Methods: A cross-sectional design with a sample of 67 respondents. Used Parenting Stress Scale questionnaire and the knowledge level questionnaire. The validity test was conducted on 30 respondents at Ananda therapy school with the results of the stress level questionnaire as many as 14 valid statement items, the knowledge level questionnaire 20 valid statements. Results: The results of the analysis of age characteristics with stress levels obtained a p-value of 0.534> α0.05, the results of economic status with stress levels obtained a p-value of 0.871> α0.05, the results of the level of education with stress levels obtained a p-value of 0.402> α0.05 and the results of the analysis of the level of knowledge with stress levels obtained a p-value of 0.389> α 0.05. Conclusion: There was no relationship between the characteristics of age, economic status, level of education and level of knowledge of mothers with the level of stress in caring for autistic children. Abstrak Latar Belakang: Autistic Spectrum Disorder merupakan penyakit perkembangan yang tidak dapat disembuhkan. Orangtua yang memiliki anak autis harus memiliki kemampuan dalam merawat, sebab memiliki perbedaan khususnya dalam bersosialisasi, sehingga orangtua mengalami stress dalam merawat. Tujuan: Untuk menganalisis hubungan karakteristik orangtua dan tingkat pengetahuan ibu dengan tingkat stress dalam merawat anak autis di kota bekasi. Metode: Desain cross-sectional menggunakan purposive sampling dengan sampel 67 responden. Menggunakan kuesioner Parenting Stress Scale dan kuesioner tingkat pengetahuan ibu. Uji validitas dilaksanakan pada 30 responden di sekolah terapi Ananda dengan hasil kuesioner tingkat stress sebanyak 14 item pernyataan valid, kuesioner tingkat pengetahuan 20 pernyataan valid. Hasil: Hasil dari analisis karakteristik usia dengan tingkat stress didapat p-value yaitu 0,534 > α 0,05, hasil dari status ekonomi dengan tingkat stress didapatkan p-value sebesar 0,871 > α 0,05, hasil dari tingkat pendidikan dengan tingkat stress didapatkan p-value sebesar 0,402 > α0,05 dan hasil dari analisis tingkat pengetahuan dengan tingkat stress didapatkan p-value sebesar 0,389> α 0,05. Kesimpulan: Tidak ada hubungan karakteristik usia, status ekonomi, tingkat pendidikan serta tingkat pengetahuan ibu dengan tingkat stress dalam merawat anak autis.